Autonomous Robot Driving Decision Strategy Following Road Sign And Traffic Rules: Simulation Validation - Chong, Zheng-Hao (2017)
Autonomous robot driving decision strategy following road signs and traffic rules is described using simulation with a Turtlebot [1]. A fully autonomous robot driving strategy is presented, which follows human level logic in decision making. A vision-based autonomous vehicles navigation system for road vehicles includes three main parts: 1) road and traffic signs detection; 2) vehicle movement guidance system; and 3) decision making following human level logic. The first two modules have been studied independently for many years and obtained many good results using different solutions, but there is little research in fully integrated system with high level decision making to achieve fully autonomous robot navigation following road signs. It is valuable to study and apply this concept into a real system. A simulation world is built according to real environment scenario proving the concept of study.